2023
DOI: 10.1021/acsnano.3c00422
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid Biopsy-Based Approach to Isolate and Characterize Adipose Tissue-Derived Extracellular Vesicles from Blood

Abstract: Obesity is a major risk factor for multiple chronic diseases. Anthropometric and imaging approaches are primarily used to assess adiposity, and there is a dearth of techniques to determine the changes in adipose tissue (AT) at the molecular level. Extracellular vesicles (EVs) have emerged as a novel and less invasive source of biomarkers for various pathologies. Furthermore, the possibility of enriching cell or tissue-specific EVs from the biofluids based on their unique surface markers has led to classifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Since an extensive characterization of plasma EVs had been performed by us in prior studies 8,10,32 , we limited the current analysis to confirm the expression of exosomal biomarkers CD63, TSG101, and Alix in urinary EVs by Western blotting ( Figure 2 ). Importantly, we did not observe any expression of endoplasmic reticulum protein Calnexin and Golgi protein GM130 in urinary EVs, confirming the purity of isolated EVs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since an extensive characterization of plasma EVs had been performed by us in prior studies 8,10,32 , we limited the current analysis to confirm the expression of exosomal biomarkers CD63, TSG101, and Alix in urinary EVs by Western blotting ( Figure 2 ). Importantly, we did not observe any expression of endoplasmic reticulum protein Calnexin and Golgi protein GM130 in urinary EVs, confirming the purity of isolated EVs.…”
Section: Resultsmentioning
confidence: 99%
“…The cargo of these vesicles relates to the pathophysiological state of the parent cells. In support of the importance of characterizing EVs as a tissue-specific biomarker, we recently reported that EVs in the plasma could inform about corresponding molecular and metabolic alterations in the visceral adipose tissues of diet-induced obese mice 8 . The relevance of these experimental observations was further strengthened by the parallel finding of augmented inflammation-related molecules in adipose tissue-derived Evs isolated from the blood of obese patients 8 .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Flow cytometry analysis was performed to evaluate the percentage of typical EV tetraspanin markers following methods and controls reported recently (Kumar et al, 2022(Kumar et al, , 2023Mishra et al, 2023)…”
Section:  Flow Cytometrymentioning
confidence: 99%